Integrated renewable energy micro-grid for meeting peak hours demand - Aznan K.A.; Khan S.; Yaacob M.; Khalifa O.O.; Aboadla E.; Tohtayong M.; Khalil A.; Muhaisen N.A.N.; Tan N.M.L. (Institution of Engineering and Technology, 2023)
Electric utilities; Energy dissipation; Voltage distribution measurement; Alternative source; Conventional systems; Energy demands; Low voltage distribution network; Power demands; Renewable energies; Renewable energy source; Solar and winds; Renewable energy resources